Editor’s Foreword, Volume 51 2022 - Karacic, Steve (Proceedings of the Seminar for Arabian Studies, 2022)
The Seminar for Arabian Studies is the longest continually running academic forum for the presentation of cultural heritage research on the Arabian Peninsula. Meeting for the first time in 1968, the Seminar covers a wide range of subjects including but not limited to archaeology, epigraphy, history, ethnography, art, architecture, linguistics, and literature from prehistory to the early twentieth century. The 54th Seminar for Arabian Studies consisted of 73 papers and 6 posters presented over the course of two weekends. These papers included four special sessions: a session on the recent research in North West Arabia, two sessions on the historical and cultural relations between Iberia and Arabia, and one session on maritime practices. The special sessions on North West Arabia and Iberian-Arabian interactions will be published as supplemental volumes while many of the papers submitted on maritime practices are included in the present issue.